Genetical, Cytological & Biological Studies of Chrysomya bezziana Vill. (Diptera: Calliphoridae) Exposed to Gamma Rays: I. Effect on Adult Emergence & Sex Ratio (Baghdad Science Journal, 2025)
the results of this study showed that irradiated pupae at age of one day old was very sensitive to all doses of gamma rays.